СТРАТЕГИЯ КОМПАНИИ И ИНТЕГРАЦИЯ ВНУТРИФИРМЕННОГО УПРАВЛЕНИЯ В ОРГАНИЗАЦИЯХ - H. K. Musapirov (Экономика: стратегия и практика, 2018)
Strategy and internal strategic compliance of integrated organizations. The purpose of this work is to develop theoretical and methodological provisions for the formation of company strategies and the creation of internally integrated organizations. The article analyzes the concepts of strategy, value and strategic correspondence of internal parts of the organization. As a result, the theoretical and methodological approach to the effective solution of problems of organizations, especially those of a strategic nature, is substantiated.The author’s conceptual model (scheme) of creating an integrated working strategy of the company (an inward view of the organization) that creates sustainable competitive advantages is presented in the article. The results of the work can be applied in the development of company strategies and the creation of integrated (internally integrated) organizations.